Analisis Kenyamanan Akustik pada Ruang Laktasi Mall di Kota Yogyakarta - Kartika Putri, Tabita Febriawaty (Nature : National Academic Journal of Architecture, 2025)
Malls are often considered the safest places to bring children, especially babies, to play due to their ideal indoor temperature and smoke-free environment. However, mothers require proper facilities such as lactation rooms to breastfeed, pump milk, or change diapers while visiting malls. Not all lactation rooms in malls take into account the aspect of auditory comfort for breastfeeding mothers. Therefore, this study aims to analyze the auditory comfort conditions of lactation rooms, using a lactation room in a mall in Yogyakarta City as the research object. The goal is to identify key aspects that should be considered in designing acoustically comfortable lactation rooms. This research involved collecting noise level data and identifying the sources and causes of noise within the lactation room. Noise measurements were conducted using a Sound Level Meter (SLM) application on a mobile phone. The results revealed that noise levels in lactation rooms in malls in Yogyakarta City still exceed the maximum recommended standard for such spaces. This condition is mainly caused by structural gaps and the use of inappropriate wall materials. These findings can serve as a reference for the design of future lactation rooms in malls and may be followed by further research on optimizing their acoustic performance.